2021
DOI: 10.1111/cyt.13020
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thyroid fine needle aspiration practice during the COVID‐19 pandemic

Abstract: Purpose To investigate the diagnostic accuracy of a different sample preparation protocol for fine needle aspiration cytology (FNAC) of thyroid nodules established during the COVID‐19 pandemic. Methods From April 2020, conventional smears during FNAC were ceased according to World Health Organization recommendations due to the increased infection risk for operators, and a new protocol using only liquid‐based cytology (LBC) was adopted. FNACs performed between April and July 2020 (COVID‐19 group) were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to the studies by Giannoula et al 32 and Vrachimis et al, 33 it has been suggested that delaying TFNAB for most asymptomatic thyroid nodules due to COVID‐19 does not negatively impact the outcomes in thyroid cancers, provided that symptoms and signs of urgent intervention are taken into account. The research by Rossi et al supports these conclusions, showing no difference in the diagnostic accuracy of TFNAB of thyroid nodules based on vaccination status and even during the pandemic 34 …”
Section: Discussionmentioning
confidence: 80%
“…According to the studies by Giannoula et al 32 and Vrachimis et al, 33 it has been suggested that delaying TFNAB for most asymptomatic thyroid nodules due to COVID‐19 does not negatively impact the outcomes in thyroid cancers, provided that symptoms and signs of urgent intervention are taken into account. The research by Rossi et al supports these conclusions, showing no difference in the diagnostic accuracy of TFNAB of thyroid nodules based on vaccination status and even during the pandemic 34 …”
Section: Discussionmentioning
confidence: 80%
“…The pandemic also helped, albeit indirectly, to overcome some of the well‐known issues of digitising a cytological slide, such as the large spread of the material on the slide leading to large‐sized WSI files, the frequent blood and foreign material contamination, and the problem of 3D‐clustering of cell groups with the need for an advanced Z‐stacking. For example, even though not in a digital setting, the pandemic has forced the use of liquid‐based cytology (LBC) methods to avoid the potential spread of the virus during a normal fine needle aspiration procedure with conventional smear preparation, and there is evidence that the diagnostic performance in terms of diagnostic yield is comparable to conventional cytology 27 . This is important because LBC preparations provide more homogenous and regular specimens which could be advantageous for WSI scanning 28 …”
Section: Figurementioning
confidence: 99%
“…For example, even though not in a digital setting, the pandemic has forced the use of liquid-based cytology (LBC) methods to avoid the potential spread of the virus during a normal fine needle aspiration procedure with conventional smear preparation, and there is evidence that the diagnostic performance in terms of diagnostic yield is comparable to conventional cytology. 27 This is important because LBC preparations provide more homogenous and regular specimens which could be advantageous for WSI scanning. 28 So, in conclusion, the pandemic has not brought us closer to a digital diagnosis in cytopathology in the same way as in surgical pathology-given that no formal approval has been licensed to WSI for diagnostic use in cytology, with CAP advocating that more evidence is required-but has definitely led to an increased awareness of the issues related to digital cytology and the potential benefits that may come from the adoption of WSI for this field of pathology.…”
mentioning
confidence: 99%
“…showed that the LBC method provided similar diagnostic results to the conventional method and can be applied during a pandemic and provide more safety. No significant differences between cytological and histological diagnoses were noticed in patients with potentially malignant lesions [ 25 ].…”
Section: How To Improve?mentioning
confidence: 99%